User experience pada Implementasi Virtual Reality sebagai Media Pembelajaran Anak Pengidap Autisme - Dea Ismy Soraya Isabella; Kurniawan Teguh Martono; Dania Eridani (Politeknik Caltex Riau, 2020)
Children with autism have a less response to stimuli that come from other people or circumstances that are around it so that children find it difficult to receive information from teachers about how to perform self-care skills compared to normal children their age. Therefore one type of learning media is needed to train the skills of children with autism in self-care. On the other hand, optimizing VR technology as a learning media about self-care for children with autism is still limited. This Human Centered Design (HCD) method is used in making User experience on VR as a learning media for children with autism. The flow of research starts from the study of literature, analysis of usage context, analysis of user needs, making solution designs, evaluating solution designs, results and conclusions. User experience Questionnaire (UEQ) was chosen as a measure and evaluation of application user experience because UEQ allows rapid assessment of a product and data analysis tools are available. The results of research conducted at SLB Negeri Semarang and SLB Putra Mandiri show the average value obtained from the evaluation of user experience applications using UEQ namely at Attractiveness of 1.41, Perspicuity of 1.80, Efficiency of 1.28, Dependability of 1 , 80, Stimulation of 1.49, Novelty of 1.39, and it can be concluded that the design according to the UEQ scale has a positive user experience because all scales above 0.8.